Does Rotavirus Vaccination Affect Longer-Term Intussusception Risk in US Infants?. (14th June 2019) - Burke, Rachel M; Tate, Jacqueline E; Dahl, Rebecca M; Aliabadi, Negar; Parashar, Umesh D
Abstract: Rotavirus vaccination has been associated with a short-term increased risk of intussusception. Our analysis of insurance claims for 1 858 827 US children with 544 recorded cases of intussusception found a nonsignificant decrease in intussusception (hazard ratio, 0.79 [95% confidence interval, 0.57–1.09]) in fully rotavirus-vaccinated children followed up to the age of 2 years.